Long-term outcomes of hyperbaric oxygen pretreatment in autologous hematopoietic stem cell transplantation - Lococo, Vinny; Okoniewski, Maire; Shoaib, Abdalla; Shune, Leyla; Abhyankar, Sunil; Singh, Anurag; Allin, Dennis; Ansari, Briha; McGuirk, Joseph; Aljitawi, Omar S.; Abdelhakim, Haitham (Frontiers in Hematology, 2026)
Autologous hematopoietic stem cell transplantation (aHSCT) is an effective treatment for hematologic malignancies. Hyperbaric oxygen (HBO) pretreatment has demonstrated safety and feasibility, improved neutrophil engraftment, and reduced mucositis in patients undergoing aHSCT. This was a retrospective review comparing 19 patients who completed HBO therapy prior to aHSCT with a 225-patient historical control cohort. Median overall survival was not reached in the HBO cohort and was 9 years in the historical control cohort (p = 0.59). Median relapse-free survival was 4.2 years in the HBO cohort and 3.7 years in the historical cohort (p = 0.34). The HBO cohort had a lower cumulative incidence of non-relapse mortality, although the difference was not statistically significant (p = 0.057). Excluding non-melanoma skin cancers, the incidence of secondary malignancy was reduced in the HBO cohort (5.26% vs. 22.07%, p = 0.074). Rates of organ damage were reduced in the HBO cohort but did not reach statistical significance (47.4% vs. 61.3%, p = 0.12). Rates of cardiac (5.3% vs. 23.9%; p = 0.046) and renal (15.8% vs. 42.8%; p = 0.016) organ damage were significantly reduced in the HBO cohort. There was less autoimmune disease observed in the HBO cohort compared with the historical control cohort (0.0% vs. 7.69%; p = 0.14). Overall, HBO therapy before aHSCT showed trends toward lower non-relapse mortality and a lower incidence of secondary malignancy. The incidence of cardiac and renal damage was significantly reduced. These findings indicate that HBO is well tolerated and may improve outcomes in patients undergoing aHSCT.